ANALISIS PEMAHAMAN SISWA TENTANG KONSEP PENGAMALAN PANCASILA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI KELAS II SDN SUKASARI I CIBUAYA KARAWANG - Rani Fitriyani; Tarpan Suparman; Ayu Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted because students' understanding of the concept of practicing Pancasila at SDN Sukasari I Cibuaya Karawang is still low. Based on observation data and initial tests, as many as 15 people (75%) of the 20 students studying were still below the KKM. The aim of this research is to deepen students' understanding of the application of Pancasila values ​​in learning Pancasila Education according to the Merdeka Curriculum in class II SDN. Sukasari I Cibuaya Karawang. The learning model used works the same as the pair learning type. This research uses the research method used is a descriptive qualitative method. Determining the subjects of this research used a purposive sample. To help students understand the concept of practicing Pancasila at SDN Sukasari I Cibuaya Karawang, the make a match cooperative learning model is used. The research results showed a significant increase from only 15 under the KKM, to 18 students.